2013
DOI: 10.1522/030585422
|View full text |Cite
|
Sign up to set email alerts
|

Big Five personality factors and individual performance /

Abstract: Personality provides a measure of how an individuals thinks, communicates with other people, reacts to different situations, deals with stress, sets goals, works to achieve those goals as well as how he/she analyzes information and handles situations. During the past century numerous researchers have attempted to identify the role of personality in several indicators of career success (such as job performance and satisfaction) and occupation matching. Psychological researchers have regrouped a number of major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
(81 reference statements)
1
4
0
Order By: Relevance
“…As found in previous studies, extraverted personality tend to be happier in their jobs and suffer lower levels of job stress (Attia, 2013). Birch & Kamali (2001) concluded that extroversion dimension of personality had a negative relationship with job stress, anxiety and depression, that directly supports the finding in this study.…”
Section: Hypotheses Testingsupporting
confidence: 90%
See 3 more Smart Citations
“…As found in previous studies, extraverted personality tend to be happier in their jobs and suffer lower levels of job stress (Attia, 2013). Birch & Kamali (2001) concluded that extroversion dimension of personality had a negative relationship with job stress, anxiety and depression, that directly supports the finding in this study.…”
Section: Hypotheses Testingsupporting
confidence: 90%
“…This finding is supported by previous researches that states job stress have high magnitude of influence by conflict (Hendrix, 1989, as cited in Roberts et al,. 1997), work environment (Quick et al, 1997), neuroticism (Watson & Pennebaker, 1989;Birch & Kamali, 2001) and negatively in relationship with extraversion (Birch & Kamali, 2001;Attia, 2013).…”
Section: Regression Analysis On Coping Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conscientiousness and agreeableness (intrinsic qualities) are most highly related to GPA (Komarraju et al , 2011). Conscientiousness correlated with grades most consistently; obversely, extraversion (an extrinsic characteristic) showed negative correlation with grades (Attia, 2013).…”
Section: Resultsmentioning
confidence: 96%